The Relationship Between Ethical Leadership and Employee Job Satisfaction: The Mediating Role of Media Richness and Perceived Organizational Transparency - Guo, Kaimeng (Frontiers in Psychology, 2022)
Ethical leadership (EL) is a vital component driving firms’ practice, significantly affecting employee satisfaction (ES). The objective of this study was to investigate the relationship between EL and employee job satisfaction. Moreover, the study investigates the mediating effect of media richness (MR), perceived organizational transparency (OT) on EL, and ES. In addition, the study used a convenient sampling technique for collecting the data from 276 employees working in the service sector of Macau. Essentially, questionnaires had used as the fundamental tool guiding the data collection method. The findings indicate a positive and significant relationship between EL, ES, MR, and perceived OT. The MR and perceived OT have significant mediating effects between EL and ES. The study is beneficial for the service sector of Macau to plan the strategies for their employees in terms of organizational sustainability and success. The study is also helpful for the government to understand EL and for the researcher to search the new aspects of EL in organizations for future research direction.